Decision Making And Service Innovation Of Mobile Banking: Creation Of Sustainable Competitive Advantage - Wong, Lip Soon (2006)
This is a qualitative empirical research based on new service development (NSD) of mobile banking (MB). In this study, 120 respondents were approached and they were driven through three phases. The objective of this study were i) to identify current issues concerning MB and NSD; ii) to adopt and refine multidisciplinary qualitative methodology based on grounded theory method; iii) to elicit opinions on the key decision-making practices that influence the organisational service innovation capabilities (OSIC); and iv) to determine the qualitative factors in the OSIC that affect the robustness of an organisation to fit and withstand the conditions of different sustainable competitive advantage (SCA) models.